Application of litters to inhibit nitrification in Vertisols on sweet corn (Zea mays S.) - Supriyadi Supriyadi; Adiprasetya Widyatama; Gadis Mona Prinandhika; Purwanto Purwanto; Sri Hartati (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2021)
Nitrification, or the process of oxidation of ammonium to nitrate in the soil, needs to be inhibited because it reduces the efficiency of nitrogen fertilizers. Vertisols have 2:1 minerals and have high negative charge, so ammonium is more absorbed by soil particles, whereas nitrate is free to move in the soil and diffuses into the plant tissue or is leached with gravity water. This study aimed to determine the litter treatment that can inhibit the nitrification process in Vertisols on sweet corn plants. This research was conducted in June until November 2019 in the Plastic House of Plesungan, Gondangrejo, Karanganyar, Indonesia. This study used a basic completely randomized design with a single factor (litter type) as an immobilizer. The types of litter used in this study were Gliricidia maculata, Albizia falcataria, Senna siamea, and Tithonia diversifolia. The parameters observed were ammonium content, nitrification potential, average nitrate content, actual nitrification, plant height, number of leaves, and dry crown plant. Tithonia diversifolia gave the highest actual nitrification of 23.26%. Senna siamea has the lowest actual nitrification of 12.36%, followed by Gliricidia maculata with 17.39% and Albizia falcataria with 17.67%. This shows that the Tithonia diversifolia litter has the highest value in inhibiting nitrification. Maize plants treated with the Tithonia diversifolia litter had the best plant growth compared to those applied with other treatments. Therefore, among the treatments used, the Tithonia diversifolia litter was most optimal in inhibiting nitrification in Vertisols.